Seasonal Variation in Blood Pressure in 162, 135 Patients With Type 1 or Type 2 Diabetes Mellitus. Issue 4 (10th December 2015) - Hermann, Julia M.; Rosenbauer, Joachim; Dost, Axel; Steigleder‐Schweiger, Claudia; Kiess, Wieland; Schöfl, Christof; Holl, Reinhard W.
Abstract : Seasonal variation in blood pressure (BP) has been observed in different populations. However, only few studies have focused on BP seasonality in diabetic patients. This study examined the seasonal patterns in BP in 62, 589 patients with type 1 diabetes mellitus (T1DM) and in 99, 546 patients with type 2 diabetes mellitus (T2DM) from the German/Austrian Diabetes Follow‐up Registry. Adjusted mean BP values revealed seasonal cycles of 12 months, with higher BP in colder months. Using harmonic regression models, the estimated systolic BP difference throughout the year was 2.28/2.48 mm Hg in T1DM/T2DM (both P <.001). Interestingly, seasonal variation in diastolic BP was larger in T1DM than in T2DM (1.24/0.64 mm Hg, P <.001). A sex difference was observed in T1DM only, while age differences occurred in both types of diabetes. Correlations between BP and potentially related factors such as outdoor temperature indicated that reasons underlying BP seasonality are likely to be complex and vary by subgroup.